Development of a Virtual Assistant for Alerts and Notifications in a Learning Environment - Amaral, Ygor; Rodrigues, Rodrigo L.; Maciel, Alexandre M. A. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2015: Anais do XXVI Simpósio Brasileiro de Informática na Educação, 2015)
Increasingly, learning platforms have been part of the daily lives of teachers and students, either in a distance environment, either in a face to face learning. Several initiatives have been undertaken in order to provide resources that can enhance communication and interaction in educational contexts. Despite these efforts, confusing content offered by these platforms can often cause adverse effects such as lack of engagement, or in more severe cases, dropouts. In this scenario emerged the Avatar Education, an animated virtual assistant with synthetic voice to support online learning, integrated with LMS Moodle. This work aims to present the process of design, development and evaluation of a mobile module of Avatar Education as a way to improve communication and interaction with the platform. For its realization, a process of requisites survey and validation was conducted with users and experiments based on interviews served to validate the quality of the obtained solution. The results were promising and encourage the growth of new features to increasingly improve communication and interaction.